1999
DOI: 10.1108/09513549910278124
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between college experience and academic performance among minority students

Abstract: A number of factors have been identified as important to the retention and success of minority students in American higher education. Foremost among these factors are college experience variables like academic integration and social integration. The purpose of this study was to model the relationship between college experience and academic performance for minority students enrolled in an American institution of higher learning. Using structural equation modeling techniques, a model of the college experience co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 25 publications
1
43
2
Order By: Relevance
“…The usage of library is another factor affecting the academic performance. Saenz et al (1999) revealed using the library for quiet studying is positively associated with higher GPA.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The usage of library is another factor affecting the academic performance. Saenz et al (1999) revealed using the library for quiet studying is positively associated with higher GPA.…”
Section: Discussionmentioning
confidence: 99%
“…According to Saenz et al (1999) Positive experience with the educational equity program was positively associated with higher GPA. Another finding reveals that self-motivation as a factor that positive relate with academic success (Hedjazi & Omidi, 2008cited by Harb & El-Shaarawi, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…An oft-cited article by Mallinckrodt and Sedlacek (1987) found a positive correlation between hours spent in campus libraries and student retention in a comparative study of African American students at the University of Maryland. Saenz et al (1999) developed a model of the relationship between college experience and academic performance for the retention and success of U.S. minority students. College experiences that influenced retention were described as variables affecting academic and social integration.…”
Section: Literature Reviewmentioning
confidence: 99%